A Study on the Role of Precision Agriculture in Agro-Industry - Siddegowda C. J.; A.Jayanthila Devi, (International Journal of Applied Engineering and Management Letters (IJAEML), 2021)
Purpose: Agriculture is a vast field that necessitates the assistance of disciplines from other fields in order to properly grow. In recent days Information technology is been used in agriculture that helps in the efficiency of the growth of the productivity of agriculture such as in the development of the quality of the farming and its products Precision agriculture are used to increase the growth of the crop quantity. In this paper, a survey includes the analysis and application of precision agriculture. Precision agriculture is used to increase the growth of the crop quantity. And various Precision agriculture companies that have helped the farmer in the field growth. Objectives: To study the role of Information Technology used in Agriculture, and view on various techniques used in precision agriculture. Methodology/Design/Approach: The analysis and the application of precision agriculture are done by referring various research paper, articles. A Literature Survey is done. Findings/Result: Farmers are currently hesitant to use the new Techniques, when compared to traditional farming, Precision farming has the potential to produce higher yields. Originality/value: Based on the secondary data available, the paper focus on the application of precision agriculture. Findings/Result: To study the role of Information Technology used in Agriculture, Precision Agriculture.